2011 IEEE Forum on Integrated and Sustainable Transportation Systems 2011
DOI: 10.1109/fists.2011.5973632
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental factors on speed choice

Abstract: Speed and homogeneity of speed are important factors for safe and sustainable traffic. Lower speeds and more homogeneous speeds are safer and cause less pollution. Speed behavior is influenced by environmental factors as well as by personal factors. Understanding the relation between speed behaviour and the influencing factors offers clues for appropriate countermeasures against inappropriate and excessive speed.This study investigates the relation between speed and environmental factors for single lane rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Older drivers have reported feeling pressured to go with the flow of the traffic rather than remaining at or below the speed limit, even while having a special device in their vehicle that warned them about their speeding (Porter & Ash, 2008). Homogeneity of speed across all drivers on a specific roadway is important for safety, with large differences between speeds of vehicles creating a safety hazard (Aarts et al, 2011), so there is logic in their speed choices if almost everyone else is speeding (European Conference of Ministers of Transport, 2006;Feng, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older drivers have reported feeling pressured to go with the flow of the traffic rather than remaining at or below the speed limit, even while having a special device in their vehicle that warned them about their speeding (Porter & Ash, 2008). Homogeneity of speed across all drivers on a specific roadway is important for safety, with large differences between speeds of vehicles creating a safety hazard (Aarts et al, 2011), so there is logic in their speed choices if almost everyone else is speeding (European Conference of Ministers of Transport, 2006;Feng, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Enforcement as well as various road features (e.g., width, surface, number of lanes, straightness, proximity of trees, etc.) may also influence speeding behaviour (Aarts, Brandenburg, & Van Nes, 2011).…”
mentioning
confidence: 99%
“…Furthermore, the perceived task demand is not equal for all drivers. Aarts et al (2011) found that speed percentiles were less homogeneous on narrowed roads, and narrower work zone lanes were also associated with increased ratings of stress and difficulty and were pointed out by drivers as one of the factors that make for difficult driving in work zones (Petzoldt et al, 2016). According to Fuller (2005), when a task demand exceeds the driver's perceived capability, the driver will probably be unable to avoid an obstacle or stop in time.…”
Section: Functional Models Of Driving Behaviourmentioning
confidence: 99%